2019
DOI: 10.1513/annalsats.201810-651sr
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss for Children and Adults with Obesity and Asthma. A Systematic Review of Randomized Controlled Trials

Abstract: Background: Asthma and obesity are major public health problems, affecting hundreds of millions of people worldwide. Obesity is associated with increased asthma risk and severity, and lower asthma-related quality of life. Objective: In this systematic review, we aimed to evaluate whether weight loss in subjects with obesity and asthma leads to improvement in asthma-related outcomes. Data Sources and Extraction: We searched PubMed and Google Scholar for all studies in English published January 2000-December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 46 publications
(92 reference statements)
1
61
0
6
Order By: Relevance
“…The pathophysiology of the asthma-obesity link is complex and involves mechanical [6], cytokine-mediated [6,7] and genetic factors [6,8], with complex genetic-environmental interactions [6]. Furthermore, weight-loss interventions have shown improvement in asthma outcomes [9][10][11]. In a recent meta-analysis of randomised clinical trials (RCTs) of weight-loss interventions, OKONIEWSKI et al [11] reviewed four RCTs in children and six in adults of weight-loss interventions in obese asthmatics and concluded that, while the available studies are not uniform, weight loss leads to improvement in asthma-related quality of life, asthma control and lung function.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of the asthma-obesity link is complex and involves mechanical [6], cytokine-mediated [6,7] and genetic factors [6,8], with complex genetic-environmental interactions [6]. Furthermore, weight-loss interventions have shown improvement in asthma outcomes [9][10][11]. In a recent meta-analysis of randomised clinical trials (RCTs) of weight-loss interventions, OKONIEWSKI et al [11] reviewed four RCTs in children and six in adults of weight-loss interventions in obese asthmatics and concluded that, while the available studies are not uniform, weight loss leads to improvement in asthma-related quality of life, asthma control and lung function.…”
Section: Introductionmentioning
confidence: 99%
“…One of the approaches to manage obesity-related asthma is to address body weight. Some weight-loss studies conducted in children, 88 but not all, 23 have shown an improvement in asthma disease burden, including improvement in pulmonary function, although there was no change in systemic inflammation. 88 These findings differed from pre and post studies on adult bariatric surgery patients where in addition to improvement in airway responsiveness 89 and lung volumes, 90 there was an improvement in systemic inflammatory measures which correlated with improvement in pulmonary function, supporting a role of systemic immune responses in the obese asthma phenotype.…”
Section: Management Of Obesity-related Asthma: Need For a Differentmentioning
confidence: 95%
“…Cumulative weight gain over time is associated with asthma‐like symptoms, such as wheeze . Therefore, weight loss is associated with smaller and less consistent improvements in asthma outcomes in children relative to adults . Ethnic differences may stem from differences in body fat distribution, particularly in light of the contribution of truncal adiposity to the obese‐asthma link .…”
Section: Obesity and Asthma: A Causal Associationmentioning
confidence: 99%
See 2 more Smart Citations